Evaluation of Efficiency of 25% Oral Sucrose on Pain Reduction due to Hepatitis B Vaccination in Newborns: A Randomize Clinical Trial - Saadati H; Fakehi F; Sangsefedi Z; Mirzarahimi M; Mohammadzadeh A; Saeedi R (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2010)
Background and Objectives: The ability of neonates to perceive and react to pain has recently been acknowledged. Sweet solutions are one of the recommendations for pain relief in newborns. The aim of this study was to investigate the effect of oral sucrose for reducing the intensity of pain during HB vaccination in newborns.Methods: In this clinical trial and double blinded study 70 healthy neonates vaccinated with HB vaccine on the first day of birth were randomly divided into experimental (35) and control groups (35).The experimental group received 2ml 25% sucrose solution 2 minutes before the procedure and the control group received 2ml water for injection. Responses of pain were estimated by the Neonatal Infant Pain Scale (NIPS). Data were analyzed using Chi-square tests, T and Mann-Whitney tests. Results: Change in breathing pattern, facial expression, state of arousal and state of organs in infants occurred in both groups. Only one neonate in sucrose group had low score. The pain score in one neonate was 6 and other scores were 7. In the control (water group) group, scores of all neonates were 7. There was no significant difference between the two groups. Conclusion: HB vaccination is a painful procedure and receiving 2ml sucrose before injection can not reduce indices of pain.